Interleukin 1β Mediates the Pathogenesis of Nasal Mucosal Epithelial Barrier Dysfunction in Allergic Rhinitis - Wang H; Song X; Wang Y; Yang T; Liu W; Mou Y; Ren C; Song X (Dove Medical Press, 2024)
Hanrui Wang,1- 4,* Xiaoyu Song,1- 4,* Yao Wang,1- 4 Ting Yang,1- 4 Wanchen Liu,1- 4 Yakui Mou,1- 4,* Chao Ren,1- 5 Xicheng Song1- 4 1Department of Otorhinolaryngology, Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China; 2Shandong Provincial Key Laboratory of Neuroimmune Interaction and Regulation, Yantai Yuhuangding Hospital, Yantai, People's Republic of China; 3Shandong Provincial Clinical Research Center for Otorhinolaryngologic Diseases, Yantai Yuhuangding Hospital, Yantai, People's Republic of China; 4Yantai Key Laboratory of Otorhinolaryngologic Diseases, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China; 5Department of Neurology, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xicheng Song; Chao Ren, Yantai Yuhuangding Hospital, Qingdao University, No. 20, East Road, Zhifu District, Yantai, 264000, People's Republic of China, Tel +86535 6691999, Fax +86535 6240341, Email drxchsong@163.com; renchaotg@126.comBackground: The nasal mucosal epithelial barrier is the primary site of allergic rhinitis (AR). Interleukin-1β (IL-1β), as a crucial factor in immune inflammation, not only plays a crucial role in hypersensitivity reactions but also affects the digestive mucosa and skin epithelial barrier. However, the role of IL-1β in the nasal mucosal epithelial barrier in AR has not been reported, and this study aimed to investigate the effect and possible mechanisms involved.Methods: Dermatophagoides pteronyssinus 1 was used as an allergen to construct an AR mouse model and stimulate human nasal mucosal epithelial cells (HNEpCs) and observe the expression changes of IL-1β and epithelial barrier indicators CLDN1 and OCLN in mouse nasal mucosa and HNEpCs. Then, the possible mechanisms of action were explored via exogenous IL-1β stimulation and pharmacological inhibition of IL-1β or its receptor interleukin-1 receptor type 1 (IL-1R1).Results: The results showed that Dermatophagoides pteronyssinus 1-primed mouse nasal mucosa or human HENpCs had increased expression of IL-1β and decreased CLDN1 and OCLN, and IL-1β could directly lead to reduced expression of epithelial barrier indexes in HNEpCs. In addition, inhibition of IL-1β or IL-1R1 can effectively alleviate the damage to the epithelial barrier.Conclusion: IL-1β has a destructive effect on the nasal mucosal epithelial barrier in AR, and inhibition of IL-1β or its receptor IL-1R1 can effectively protect the nasal mucosal barrier. IL-1β is a potential target for the treatment of AR.Keywords: interleukin-1β, allergic rhinitis, nasal mucous membrane, epithelial barrier, DerP1